Calculations in chemistry - Dahm, Donald J.
Recent research has documented that in K–12 programs over the past decade, instruction in math computation has been de-emphasized. Calculations in Chemistry addresses these gaps in student background, applying the findings of recent scientific research on cognition, fluency in applied mathematics, and reading comprehension, to prepare students for the rigor and pace of general chemistry